2018
DOI: 10.1016/j.molcel.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

FUS Regulates Activity of MicroRNA-Mediated Gene Silencing

Abstract: MicroRNA-mediated gene silencing is a fundamental mechanism in the regulation of gene expression. It remains unclear how the efficiency of RNA silencing could be influenced by RNA-binding proteins associated with the microRNA-induced silencing complex (miRISC). Here we report that fused in sarcoma (FUS), an RNA-binding protein linked to neurodegenerative diseases including amyotrophic lateral sclerosis (ALS), interacts with the core miRISC component AGO2 and is required for optimal microRNA-mediated gene silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 59 publications
1
56
0
1
Order By: Relevance
“…smFRET via TIRF Microscopy. Single-molecule imaging was performed as previously described by Zhang et al (83).…”
Section: Methodsmentioning
confidence: 99%
“…smFRET via TIRF Microscopy. Single-molecule imaging was performed as previously described by Zhang et al (83).…”
Section: Methodsmentioning
confidence: 99%
“…One of the best studied proteins that undergoes LLPS in vitro and in vivo is Fused in Sarcoma (FUS) (Hofweber et al, 2018;Kang et al, 2019;Kato et al, 2012;Monahan et al, 2017;Murray et al, 2017;Patel et al, 2015;Schwartz et al, 2013). FUS is an ubiquitously expressed RNA-binding protein that has been implicated in diverse RNA metabolic pathways, such as transcription, pre-mRNA splicing and miRNA processing (Meissner et al, 2003;Raczynska et al, 2015;Reber et al, 2016;Schwartz et al, 2012;Yu and Reed, 2015;Zhang et al, 2018). In 2009, mutations in FUS were shown to be causative for Amyotrophic Lateral Sclerosis (ALS) (Kwiatkowski et al, 2009;Vance et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies highlighting the interactions of miRISC components with proteins involved in neurodegenerative disorders, such as HTT, FUS, and Ataxin points toward an important role of miRISC composition in the pathology of these disease which should be investigated in detail (Savas et al, 2008;McCann et al, 2011;Zhang T. et al, 2018). Further, the above-mentioned studies showed that mutant versions of HTT and FUS impair miRNA mediated silencing, providing further evidence for the role of miRISC composition in driving neurodegenerative disorders (Savas et al, 2008;Zhang T. et al, 2018). All these studies indicate that it is not miRNA alone, but the composition of miRISC has a great significance in the pathophysiology of disorders of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…These RBPs either associate directly with miRISC to influence its function, or they modulate miRISC activity by binding close to the miRNA binding site in the target mRNAs. Proteins like Fragile X Mental Retardation Protein (FMRP), MOV10 Moloney leukemia virus 10 (MOV10), Ataxin 2, and Fused in Sarcoma (FUS) directly associate with core miRISC to influence its downstream effector functions (Banerjee et al, 2009;McCann et al, 2011;Muddashetty et al, 2011;Sudhakaran et al, 2014;Zhang T. et al, 2018) (Figures 1D,E). The association of FMRP with miRISC was earlier contested as one of the report has shown that FMRP does not associate with miRISC and is an important component of stress granules (Didiot et al, 2008).…”
Section: Diverse Mirisc Composition and Its Regulation Brings About Tmentioning
confidence: 99%